KONVERSI BANK KONVENSIONAL MENJADI BANK SYARIAH DITINJAU DARI HUKUM POSITIF DAN HUKUM ISLAM - Cut Nova Rianda (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2018)
The phenomenon of industrial development of Islamic Banking in Indonesia after the Act No. 10 of 1998 concerning Amendment to Law No. 7 of 1992 took place with so rapidly. This happens because in the era of the Law No. 1998 banking law development policies using dual banking system (dual banking system), the permissibility of conventional commercial banksprovider the service with the first form of Islamic Sharia (UUS). Provision of services easier by the existence of sharia office channeling concept (use of conventional commercial banks in servicing transactions with Islamic Laws, provided that the bank in question has had Sharia or abbreviated by the term UUS) as introduced in the Bank Indonesia Regulation (PBI) Amandement No. 8/3/PBI/2006 Operations Conventional Commercial Banks to Commercial Banks Conducting Business Based on Sharia Principles and Office Opening Bank Conducting Business Based on Sharia Principles by Conventional Commercial Banks as amended by Regulation No. 9/7 / PBI/2007. The core of the office channeling is that it allows a conventionalbank or conventional bank branches providing Islamic services without the need to first establishUUS but simply provides a special unit in the office of the bank in the form of a counter question.